EVALUASI KINERJA BATIK SOLO TRANS (STUDI KASUS : KORIDOR I KARTASURA-PALUR, SURAKARTA) - Nadhia Puspita Rachma; Purnomo Dwi S.; Ismiyati Ismiyati; Wahyudi Kushardjoko (Jurnal Karya Teknik Sipil, 2013)
Batik Solo Trans (BST) included in the category of Bus Rapid Transit, this modes of transportation provided by the government to transportation of Surakarta, but the society not interest with this mode. This study was conducted to determine the publics preference for mass transit and investigate the performance in terms of Batik Solo Trans department of transportation standards and world bank standards. The research method used survey and give questionnaire toward users and non users BST. The evaluation results of BST corridor I performance got some indicators which have department of transportation standards and world bank standards there are headway, speed, distance time on Saturday and Sunday, and 67% the shelter distance, beside for load factor still under standard 70%, load factor could not full filled, based on questionnaire result, society not interest use BST because some reason, for example wasting time, incomplete route and facility of BST, long distance time, which evidenced based on survey result more than 3 hours on Monday. Although load factor is less based on BOK analysis with tariff  of BST got profit can used for maintenance and addition of the bus. The analysis results, system can be improve appropriate with the expectation of the society, there are addition corridors than intersect corridor other, lane BST, beheading route corridor I have small load factor, the transportation other can be the feeder, apply contra flow system on Slamet Riyadi road and bus priority tracking at intersections for shorten distance time.